Implementasi Ajaran Tri Hita Karana Sebagai Upaya Pembentukan Karakter Peduli Lingkungan Bagi Siswa di SDN 3 Sesetan - Mardiana, I Made (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
This study aims to describe the implementation of the Tri Hita Karana teaching as an effort to develop environmental awareness character among students at SDN 3 Sesetan. Tri Hita Karana is a local wisdom in Hinduism that emphasizes harmonious relationships between humans and God (parhyangan), fellow humans (pawongan), and the natural environment (palemahan). This research employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The results indicate that the implementation of Tri Hita Karana is carried out through routine activities such as communal prayers, school environmental clean-up programs, and reinforcing the value of togetherness during learning. Additionally, teachers actively integrate environmental awareness values into subjects and school activities. These efforts have proven effective in shaping students' characters to be responsible for cleanliness, concerned about the natural surroundings, and cooperative. Therefore, the Tri Hita Karana teaching serves as an essential foundation in instilling eco-pedagogical values and fostering a generation that is environmentally conscious from an early age.